Health economics aspects of kidney transplantation in Sicily: a benchmark analysis on activity and estimated savings - Cacciola, Roberto; Leonardis, Francesca; Gitto, Lara; Favi, Evaldo; Gruttadauria, Salvatore; Clancy, Marc; Veroux, Massimiliano; Angelico, Roberta; Pagano, Duilio; Mazzeo, Carmelo; Cacciola, Irene; Santoro, Domenico; et al. (Frontiers in Public Health, 2023)
Background International and national registries consistently report substantial differences in kidney transplant (KT) activity despite demonstrable clinical and financial benefits. The study aims to estimate the financial resources gained by KT and produce a benchmark analysis that would inform adequate strategies for the growth of the service. Methods We analyzed the KT activity in our region between 2017 and 2019. The benchmark analysis was conducted with programs identified from national and international registries. The estimate of financial resources was obtained by applying the kidney transplant coefficient of value; subsequently, we compared the different activity levels and savings generated by the three KT programs. Findings The KT activity in the region progressively declined in the study years, producing a parallel reduction of the estimated savings. Such savings were substantially inferior when compared to those generated by benchmark programs (range €18–22 million less). Interpretation The factors influencing the reduced KT activity in the study period with the related “foregone savings” are multiple, as well as interdependent. Organ donation, access to the transplant waiting list, and KT from living donors appear to be the most prominent determinants of the observed different levels of activities. International experience suggests that a comprehensive strategy in the form of a “task force” may successfully address the critical areas of the service reversing the observed trend. The financial impact of a progressively reduced KT activity may be as critical as its clinical implications, jeopardizing the actual sustainability of services for patients with end-stage kidney disease.